Association Between Intermittent Hypoxia and Left Ventricular Remodeling in Patients With Obstructive Sleep Apnea-Hypopnea Syndrome - Deng, Ming; Huang, Yi-teng; Xu, Jian-qing; Ke, Xiao; Dong, Yi-fei; Cheng, Xiao-shu (Frontiers in Physiology, 2021)
The present study was undertaken to examine the association between intermittent hypoxia and left ventricular (LV) remodeling and explore which parameter of intermittent hypoxia is most relevant to LV remodeling in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). 286 patients underwent polysomnographic examination were enrolled. Based on apnea-hypoxia index (AHI), patients were divided into no, mild, moderate and severe OSAHS groups. Between-group differences in LV remodeling and the association between parameters of intermittent hypoxia and LV remodeling was evaluated. Patients with severe OSAHS were more likely to have hypertension, and higher values of LV mass (LVM) and LVM index (LVMI). In univariate regression analysis, male, body mass index (BMI), systolic and diastolic blood pressure (BP), statins, antihypertensive drugs, creatinine, and parameters of intermittent hypoxia (AHI, obstructive apnea index [OAI], lowest oxygen saturation [LSpO2], oxygen desaturation index [ODI], time spent below oxygen saturation of 90% [TS90%] and mean nocturnal oxygen saturation [MSpO2]) were associated with LVMI. After multivariate regression analyses, only male gender, BMI, systolic BP, creatinine, and ODI remained significantly associated with LVMI. Compared to those without LV hypertrophy (LVH), patients with LVH had higher ODI. Compared to patients with normal LV, concentric remodeling and eccentric LVH, those with concentric LVH had higher ODI. In conclusion, intermittent hypoxia was significantly associated with left ventricular remodeling; and among various parameters of intermittent hypoxia, ODI was the most relevant to LV remodeling.